Prevalence and Risk Factors of PSTD in Nurses Working in Intensive Care Unit - Rasheed, Nida; Batool, Afshan; Maria, Reema; Sher, Nuzhat (Biological and Clinical Sciences Research Journal, 2025)
Nurses working in intensive care units (ICUs) are exposed to high-stress environments, making them vulnerable to psychological distress, including post-traumatic stress disorder (PTSD). Identifying the incidence and associated risk factors of PTSD in ICU nurses is crucial for developing effective mental health interventions. Objective: To assess the incidence and risk factors of post-traumatic stress disorder in nurses working in the intensive care unit. Methods: A cross-sectional study was conducted in the Intensive Care Unit of Medicare Hospital, Multan from January 2024 to January 2025. A total of 100 registered nurses working in the ICU for at least 1 year were included in the study. Data was collected through questionnaires. Post-traumatic stress disorder was evaluated by the PTSD Checklist-Civilian Version. Burnout was assessed by a 22-item Maslach Burnout Inventory including questions about exhaustion, personal fulfillment, and depersonalization. A 25-item Connor-Davidson Resilience Scale to measure resilience, optimism and self-improvement. A 10-item Social Support Rating Scale was used to evaluate objective and subjective support and support utilization. Results: Among 100 nurses, the prevalence of PTSD was 20%. The mean PTSD score was 30.68 ± 10.16 with a minimum score was 10 and a maximum score of 55. The overall burnout score was 57.71 ± 7.07, 9.64 ± 2.45 for depersonalization, 23.53 ± 3.72 for exhaustion, and 26.71 ± 3.39 for personal accomplishment. There were significant differences between health status, experience, age, resilience score, and social support score in PTSD-positive and negative nurses (p<0.05). Multivariate analysis showed that burnout was independently associated with the incidence of PTSD (p=0.003) and resilience served as a protective factor. Conclusion: There is a high prevalence of PTSD among ICU nurses with burnout as an independent risk factor and resilience as a protective risk factor.